Personal Branding Atlet Muhammad Shohibul Fikri Melalui Instagram - Al Fiqri, Muhammad Rivan; Mukarom, Zaenal; Rusmulyadi, Rusmulyadi (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2023)
The research was conducted with the aim of knowing the steps for forming Shohibul Fikri's personal branding through Instagram @shohibulfikri. Personal branding can include skills, jobs, routines and so on which will make it easier for someone to recognize because they have their own characteristics. Judgments drawn from other people's thoughts will appear according to what they show. The Authentic Personal Branding model is used by Shohibul Fikri in building his own branding. This research uses a descriptive study approach and uses a constructivist paradigm with the help of primary and secondary data and data collection techniques through unstructured interviews and observation. The results of this study indicate that the personal branding activities carried out by Shohibul Fikri include four steps, namely the stage of showing authenticity, the stage of forming specialization, and the stage of showing persistence. This research resulted in the conclusion that Shohibul Fikri uses Instagram to share content that reflects himself as an accomplished, persistent, and professional young badminton athlete.